Is Embodied Cognition Bilingual? Current Evidence and Perspectives of the Embodied Cognition Approach to Bilingual Language Processing - Kühne, Katharina; Gianelli, Claudia (Frontiers in Psychology, 2019)
Accumulating behavioral and neurophysiological evidence supports the idea of language being grounded in sensorimotor processes, with indications of a functional role of motor, sensory and emotional systems in processing both concrete and abstract linguistic concepts. However, most of the available studies focused on native language speakers (L1), with only a limited number of investigations testing embodied language processing in the case of a second language (L2). In this paper we review the available evidence on embodied effects in L2 and discuss their possible integration into existing models of linguistic processing in L1 and L2. Finally, we discuss possible avenues for future research towards an integrated model of L1 and L2 sensorimotor and emotional grounding.